Installation of Audio System at Mushola Miftahul Jannah Rawakalong Village, Gunung Sindur District, Bogor Regency: Instalasi Sistem Audio Nirkabel pada Mushola Miftahul Jannah Desa Rawakalong Kec. Gunung Sindur, Kab. Bogor - Pratama Putri, Galuh Ika; Putra Sidiq, Arya; Abdul Rozak, Ojak; Supriadi , Oky; Yuwono, Fajar (CONSEN: Indonesian Journal of Community Services and Engagement, 2024)
The installation of an audio system in Miftahul Jannah mushola located in Bogor Regency aims to improve the comfort and quality of the audio system in worship activities, lectures, and other religious activities more comfortably. The audio system that is no longer feasible and does not meet SNI standards is replaced with several devices such as wireless microphones, amplifiers, speakers, and other supporting devices. This Community Service activity (PkM) uses several methods such as conducting location surveys, preparation of tools and materials, system design, implementation, and socialization. After testing the equipment, the results of the PkM activity showed that the audio system was successfully installed and the sound could be heard clearly from outside the mushola. With the installation of this new audio system, it can improve the quality of comfort in worship at Mushola Miftahul Jannah. Not only that, the PkM activities that have been carried out provide knowledge to the community about the importance of managing safe electrical installations in everyday life.